2013
DOI: 10.1111/1365-2745.12151
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic factors may explain the geographical distribution of flower colour morphs and the maintenance of colour polymorphism in the scarlet pimpernel

Abstract: Summary1. Flower colour polymorphism is traditionally attributed to pollinator selection although other factors, such as indirect selection on correlated traits, can play an important role. 2. Lysimachia arvensis is a widespread annual species with two colour morphs differing in anthocyanin composition. We explored the hypothesis that colour polymorphism is maintained by selection related to environmental heterogeneity. Morph frequencies and environmental traits were recorded in 51 populations along a wide geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
131
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(143 citation statements)
references
References 76 publications
6
131
1
5
Order By: Relevance
“…Similar mechanisms might also shape flower color polymorphisms. For example, Arista et al (2013) found that pleiotrophic effects explain the maintenance of the flower color polymorphism in scarlet pimpernel (Lysimachia arvensis), with red-flowered individuals performing better as seeds and seedlings in wetter, cooler environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar mechanisms might also shape flower color polymorphisms. For example, Arista et al (2013) found that pleiotrophic effects explain the maintenance of the flower color polymorphism in scarlet pimpernel (Lysimachia arvensis), with red-flowered individuals performing better as seeds and seedlings in wetter, cooler environments.…”
Section: Discussionmentioning
confidence: 99%
“…A key, unifying feature of recent work on the color of plant reproduction is their geographic scope (e.g., Amico et al, 2011;Arista et al, 2013;Stournaras et al, 2013;Koski and Ashman, 2015). A growing body of literature across macroecological spatial scales illustrates that variation fruit and flower colors often matches geographic variation in both biotic and abiotic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fitness relationships reversed when plants were well watered. Arista et al [27] found a similar pattern in Lysimachia arvensis, and the classic, long-term studies of Linanthus parryae suggest that environmentally variable natural selection contributes to maintenance of that blue-white polymorphism [9,68].…”
Section: Discussionmentioning
confidence: 74%
“…The rarity of high elevation white monomorphs suggests that pigment production could be among a suite of traits that promotes population persistence and expansion in high elevation sites. When other polymorphic species are subject to harsh experimental conditions, anthocyanin-rich plants often outperform anthocyanin-deficient ones, as mentioned previously [15,27]. A powerful test of this hypothesis would require data from a wider range of polymorphic species in addition to experimental manipulations that test the relationship between pigmentation and survival.…”
Section: Discussionmentioning
confidence: 99%